Frustrated Lewis pairs: A real alternative to deuteride/tritide reductions - Doubková, Sabina; Marek, Aleš (Journal of labelled compounds & radiopharmaceuticals, 2019)
Deuterium- and tritium-labeled compounds play a principal role in tracing of biologically active molecules in complicated biochemical systems. The state-of-the-art techniques using noble metal catalysts or strong reducing agents often suffers from low functional group tolerances, poor selectivity, tricky or multistep synthesis of reagents, and low specific activity of the labeled product. Herein, we demonstrate a mild and nonmetallic technique of deuteration and tritiation of polarized double bonds, such as carbonyl compounds, yielding labeled alcohols of high specific activities. This one-pot synthesis uses carrier-free hydrogen gas in situ activated by a freshly prepared frustrated Lewis pair, generating reducing reagents. This labeling strategy shows better selectivity and functional group tolerances compared with current reductive methods. Reported is an example of the selective reduction of the aldehyde moiety of 3-acetylbenzaldehyde. What makes this technology groundbreaking is its mildness, selectivity, and generation of limited amount of radioactive waste as almost no byproducts were generated after use of (B(C6 F5 )33 H)(3 HTMP) reducing reagent. Radiochemical purity of desired 3 H-labeled product in a crude reaction mixture was determined of over 94%. This work provides, to the community of radiochemists, a practical protocol for frustrated Lewis pairs (FLP)-assisted deuterium/tritium labeling technology.
Keywords: tritium; Deuterium; Lewisovy kyseliny; Isotope Labeling; izotopové značení; Catalysis; Lewis Acids; Tritium; katalýza; deuterium